2022
DOI: 10.1177/23259671211062238
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Osteoarthritis at Very Long-term Follow-up After ACL Reconstruction: A Systematic Review and Meta-analysis

Abstract: Background: Few studies on outcomes after anterior cruciate ligament (ACL) reconstruction (ACLR) have provided insight into the very long-term effects of this procedure. Purpose: To systematically review the outcomes, failure rate, incidence, and predictors of osteoarthritis (OA) for different ACLR techniques at a minimum 20-year follow-up. Study Design: Systematic review; Level of evidence, 4. Methods: A search of the PubMed, SCOPUS, and Cochrane databases was performed on June 2020 for studies of patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 38 publications
0
55
0
4
Order By: Relevance
“…In the light of the increased risk of developing symptomatic knee osteoarthritis after an ACL injury [ 17 , 25 ], it is of great importance that patients with an ACL injury remain physically active throughout life. In the present study, the included patients appeared to quit organised PA, such as football, handball, and floorball, in favour of strength training and cycling/indoor cycling, when comparing the reported type of PA from pre-injury up to 5 years after the ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of the increased risk of developing symptomatic knee osteoarthritis after an ACL injury [ 17 , 25 ], it is of great importance that patients with an ACL injury remain physically active throughout life. In the present study, the included patients appeared to quit organised PA, such as football, handball, and floorball, in favour of strength training and cycling/indoor cycling, when comparing the reported type of PA from pre-injury up to 5 years after the ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…After 15 years, the cumulative incidence of knee arthroplasty was 1.4% following cruciate ligament reconstruction and 0.2% in the matched control patients from the general population. Grassi et al 10 , in a systematic review involving 1,771 patients who had been followed for at least 20 years after ACL reconstruction, reported that TKA was performed in 1.1% of patients. Khan et al 8 , in a 20-year follow-up study involving 49,723 individuals who had undergone TKA and 104,353 controls, found that 153 (0.31%) of the patients in the TKA group had sustained an ACL injury, compared with 41 (0.04%) of the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Abram et al 7 analyzed data on >110,000 ACL reconstructions in the U.K., utilizing the national health-care records for England from 1997 to 2017, and found that 0.97% of patients with ACL reconstruction had knee arthroplasty within 10 years. Two case-control studies have suggested that ACL injury may be associated with up to 7 times greater odds of knee arthroplasty compared with the general population 8 , 9 , and a recent review presented concomitant meniscal injury as a risk factor for radiographic OA after 20 years 10 .…”
mentioning
confidence: 99%
“…Studies have shown that lower extremity injuries account for 40–80% of badminton injuries, and the anterior cruciate ligament is the most serious injury to the lower extremity [ 1 , 2 ]. As we all know, once an injury occurs, it requires a long recovery period, high costs, and unsatisfactory treatment effects, which may lead to serious sequelae, causing many athletes to end their sports careers [ 3 ]. The most common injury to the ACL is a non-contact ACL injury (70%), which usually occurs during side cuts, twists, and landings during sports.…”
Section: Introductionmentioning
confidence: 99%